Clinical and Virologic Outcomes Following Initiation of Antiretroviral Therapy Among Seroconverters in the Microbicide Trials Network-020 Phase III Trial of the Dapivirine Vaginal Ring. (22nd October 2018) - Riddler, Sharon A; Balkus, Jennifer E; Parikh, Urvi M; Mellors, John W; Akello, Carolyne; Dadabhai, Sufia; Mhlanga, Felix; Ramjee, Gita; Mayo, Ashley J; Livant, Edward; Heaps, Amy L; O'Rourke, Colin; et al.
Abstract: Background: A vaginal ring containing dapivirine, a non-nucleoside human immunodeficiency virus (HIV)-1 reverse transcriptase inhibitor (NNRTI), was safe and effective in preventing HIV-1 infection in African women. We examined the impact of dapivirine ring use at the time of HIV-1 acquisition on subsequent HIV-1 disease progression and responses to NNRTI-containing antiretroviral therapy (ART). Methods: HIV-1 disease progression and virologic failure following initiation of ART were assessed among women who acquired HIV-1 while participating in Microbicide Trials Network–020, a randomized, placebo-controlled trial of a monthly, dapivirine vaginal ring. Results: Among the 158 participants who acquired HIV-1 (65 dapivirine, 93 placebo), no differences between dapivirine and placebo participants were observed in CD4+ cell counts or plasma HIV-1 RNA over the first year after infection (prior to ART). During follow-up, 100/158 (63%) participants initiated NNRTI-containing ART (dapivirine: 39/65; placebo: 61/93); the median time to HIV-1 RNA <200 copies/ml was approximately 90 days for both dapivirine and placebo ring recipients (log-rank P = .40). Among the 81 participants with at least 6 months of post-ART follow-up, 19 (24%) experienced virologic failure (dapivirine: 6/32, 19%; placebo: 13/39, 27%; P = .42). Conclusions: The acquisition of HIV-1 infection during dapivirine or placebo treatment in ASPIRE did not lead to differences in HIV-1 disease progression. After the initiation of NNRTI-containing ART, dapivirine and placebo participants had similar times to virologic suppression and risks of virologic failure. These results provide reassurance that NNRTI-based ART regimens are effective among women who acquired HIV-1 while receiving the dapivirine vaginal ring. Clinical Trials Registration: NCT016170096 and NCT00514098. Abstract : A vaginal ring containing dapirvirine demonstrated efficacy for human immunodeficiency virus (HIV)-1 prevention. Dapivirine ring use at the time of HIV-1 acquisition did not impact the subsequent HIV-1 disease progression or responses to non-nucleoside reverse transcriptase inhibitor–containing antiretroviral therapy.